The Brazilian Network of Higher Education Institutions for Sustainable Development (Rede UniSustentável) - Rosamaria Cox Moura Leite Padgett; Joao Vitor Costa; Leonardo Chaves de Carvalho; Marcelo Augusto Santos Turine; Camila Celeste Brandao Ferreira Itavo (Journal of Sustainability Perspectives, 2024)
The Brazilian Network of Higher Education Institutions for Sustainable Development – colloquially known as UniSustentável – is a program of education, research, extension, entrepreneurship, and innovation implemented at the Federal University of Mato Grosso do Sul (UFMS). The Network aims to carry on an environment of cooperation, collaboration, exchange, and communication among member Higher Education Institutions (HEIs) with the purpose of building a more sustainable society, educating people and fostering good practice in sustainability adoption. The Network will be preferably composed of Brazilian HEIs and operates on a non-profit basis, without affiliations to political parties or religious connotations. The coordination of the Network is carried out by an elected Coordinator and Coordinator-adjunct on a biennial basis, with administrative support provided by an administrative committee and a general assembly. UniSustentável is affiliated to the Alliance of Ibero-American Networks of Universities for Sustainability and the Environment (ARIUSA). Founded in September 2023 with 3 member HEIs, as of April 2024, it has expanded to include 20 HEIs located in all 5 Brazilian regions. The network's activities are organized into working groups, each overseen by a responsible HEI and comprised of staff, faculty, and students from member HEIs, as well as the potential involvement of invited experts. Despite its short existence, UniSustentável has already demonstrated that it is possible to work towards sustainability through the collaboration of HEIs.